2017
DOI: 10.1038/s41598-017-00816-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of new Immunophenotypic Markers on Prognostic and Overall Survival of Acute Myeloid Leukemia: a Systematic Review and Meta-Analysis

Abstract: Despite technological advances, the prognosis and survival of acute myeloid leukemia (AML) adult patients remain low, compared with other hematologic malignancies. Some antigens detected by immunophenotyping may soon play a significant role in the pathophysiologic, prognostic, and overall survival (OS) rate of AML patients. Therefore, we conducted a systematic review and meta-analysis of PubMed, Scopus, Science Direct, Web of Science, and the Cochrane Library (using PRISMA guidelines). We analyzed 11 studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…However, www.nature.com/scientificreports www.nature.com/scientificreports/ topo IIβ was significantly associated with several factors that have been associated with favorable outcomes in AML, such as younger age, low CD4, CD14, CD16, CD54, CD11b, and HLA-DR, as well as with unfavorable factors, high peripheral and marrow blast percentage and increased CD7 expression. While reports on relationship or precise role of immunophenotype and prognosis in AML is controversial [25][26][27][28][29] , the association with topo IIβ but not topo IIα expression and proposed network of topo IIβ with immunophenotype markers suggests a potential role for topo IIβ expression and immunophenotype in the biology of AML. Song et al 30 reported high topo IIβ/topo IIα expression to be correlative with favorable outcome but this observation could not be compared with the present results since induction therapy utilized the anthracycline idarubicin and most patients also received hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, www.nature.com/scientificreports www.nature.com/scientificreports/ topo IIβ was significantly associated with several factors that have been associated with favorable outcomes in AML, such as younger age, low CD4, CD14, CD16, CD54, CD11b, and HLA-DR, as well as with unfavorable factors, high peripheral and marrow blast percentage and increased CD7 expression. While reports on relationship or precise role of immunophenotype and prognosis in AML is controversial [25][26][27][28][29] , the association with topo IIβ but not topo IIα expression and proposed network of topo IIβ with immunophenotype markers suggests a potential role for topo IIβ expression and immunophenotype in the biology of AML. Song et al 30 reported high topo IIβ/topo IIα expression to be correlative with favorable outcome but this observation could not be compared with the present results since induction therapy utilized the anthracycline idarubicin and most patients also received hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used prognostic factors are cytogenetic and molecular features including inv(16), t(8;21), t(15;17) as well as IDH and FLT3 mutations 24 . In addition, immunophenotyping by flow cytometry provides valuable prognostic information 5 . However, there is still room for improvement of risk assessment, and thus identification of novel biomarkers for the prediction of remission rates, risk of relapse and overall outcome holds promise to improve the treatment of AML by guiding treatment decisions 6 .…”
Section: Introductionmentioning
confidence: 99%
“…New targets to differentiate leukemic blasts from normal cells will enable more sensitive MRD analysis. These include ILT3 (CD85k) which is expressed in AML with monocytic differentiation and has high sensitivity and stable expression [ 66 ]. There are ongoing studies into AML immunotherapy which have identified a number of promising makers that differentiate leukemic cells from healthy hematopoietic stem and progenitor cells (HSPC), which could be incorporated into AML MFC MRD analysis [ 67 ].…”
Section: New and Emerging Strategies In Multiparametric Flow Cytommentioning
confidence: 99%